Development of an application for learning and teaching soccer tactics - Leser, R.; Uhlig, J.; Uhlig, M. (International Journal of Computer Science in Sport, 2009)
"Pervasive computing" in the sense of "permeating", but also in the sense of supporting human day-to-day living with computer applications has long entered the field of teaching and learning. In the area of education, developments of this kind often come up under the keyword "e-learning". Preparing teaching and learning materials based on multi-media and using interactive elements and interactivity seem especially promising when complex, dynamic, and real situations should be presented. A good example therefore, is the subject area of sports. The authors describe an e-learning system, which was developed to teach and for learning selected fields of soccer tactics based on the design-based research strategy.